1997
DOI: 10.1192/bjp.171.5.473
|View full text |Cite
|
Sign up to set email alerts
|

Weather conditions and fatal self-harm in North Cheshire 1989–1993

Abstract: Weather may influence the occurrence of FSH, probably interacting with biological and social variables. The rate of FSH death appears to be positively related to fine weather conditions, during early summer, and not to extreme weather conditions as previously reported.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
39
1
2

Year Published

1999
1999
2014
2014

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 48 publications
(43 citation statements)
references
References 13 publications
1
39
1
2
Order By: Relevance
“…More recently, studies showed that the more sunshine there is, the fewer suicides there are (Thorson and Kasworm 1984;Linkowski et al 1992), while Maes et al (1994) and Salib and Gray (1997) found the opposite to be true. In general, for every study that has correlated some element of the weather with some response indicative of emotional state, another has found opposite or contradictory results.…”
Section: Introductionmentioning
confidence: 94%
“…More recently, studies showed that the more sunshine there is, the fewer suicides there are (Thorson and Kasworm 1984;Linkowski et al 1992), while Maes et al (1994) and Salib and Gray (1997) found the opposite to be true. In general, for every study that has correlated some element of the weather with some response indicative of emotional state, another has found opposite or contradictory results.…”
Section: Introductionmentioning
confidence: 94%
“…29 Muchas otras explicaciones se han propuesto, ya que el patrón en cuanto al suicidio en el hombre durante los meses cálidos ha sido ampliamente reportado. 6,[30][31][32][33] Dentro de estas posibles explicaciones, la más plausible para BCS es la acción del calor sobre las vías que integran la percepción ambiental, información que es controlada en los circuitos de la memoria emocional, para de ahí pasar a la toma de decisiones. Las alteraciones funcionales de este circuito, aunadas a factores ambientales adversos, como el calor, parecen promover el acto suicida.…”
Section: Discussionunclassified
“…This means that beside some anthropological and biological theoretical perspectives, a wide range of competitive hypothesis could be put on the local empirical background. Thus, in addition to classical Durkheim and Morselli's theoretical positions which try to explain suicide regional variations in XIX century Europe, the Belarusian example is fit to the number of modern hypothesis operating with climatic (29,30), sociocultural and behavioral factors (31)(32)(33). Simultaneously, the question is raised about the projection of the same factors effect in genesis of alcohol psychosis regional differences.…”
Section: Discussionmentioning
confidence: 99%